INFLUENCE OF WEIGHT TRAINING ON LOWER LIMB STRENGTH IN SOCCER PLAYERS - Yu,Jie (2023)
ABSTRACT Introduction Soccer games are of long duration and more confrontational; in the second half of the game, many players have a decline in their physical level, leading to loss of matches. Objective To explore the effect of weight training on lower limb fitness in soccer players. Methods 60 athletes were included as subjects and randomly divided into control group, weight training group, and traditional physical fitness training group. All athletes trained for 45 minutes 3 times a week for 6 weeks. Before and after training, lower limb strength and proprioception were evaluated, and the strength of the knee flexor and extensor group was assessed by isokinetic muscle tester. Results Both weight training and traditional physical training were able to improve the vertical jump performance of young soccer players, the training effects of both groups were equivalent. Conclusion Weight training has the same enhancing effect as traditional physical training in terms of strength and explosive power, promoting athletic performance in youth soccer players. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.